Answer:
The product of the function f(x) = x² - 3x + 5 and g(x) =3x is;
3x³ - 9x² + 15x
Explanation:
The product of the function is simply f.g(x) = f(x).g(x)
=(x²-3x+5).(3x)
We will go ahead and open the bracket by multiplying each variable in the parenthesis by 3x
(x²-3x+5).(3x) = 3x³ - 9x² + 15x
(That is; 3x multiplied by (x²) will give 3x² , 3x multiply by(-3x) will give 9x² and 3x multiply by (5) will give 15x )
Then check if we can further simplify, since the variables are x³ , x² and x, we can no longer simplify.
So our final answer is 3x³ - 9x² + 15x
f.g(x) = 3x³ - 9x² + 15x
Therefore the product of the function f(x) = x² - 3x + 5 and g(x) =3x is 3x³ - 9x² + 15x